Nutrition before and during Surgery and the Inflammatory Response of the Heart: A Randomized Controlled Trial - Marlieke Visser; Hans W. M. Niessen; Wouter E. M. Kok; Riccardo Cocchieri; Willem Wisselink; Paul A. M. van Leeuwen; Bas A. J. M. de Mol (Journal of Nutrition and Metabolism)
Major surgery induces a long fasting time and provokes an inflammatory response which increases the risk of infections. Nutrition given before and during surgery can avoid fasting and has been shown to increase the arginine/asymmetric dimetlhylarginine ratio, a marker of nitric oxide availability, in cardiac tissue and increased concentrations of branched chain amino acids in blood plasma. However, the effect of this new nutritional strategy on organ inflammatory response is unknown. Therefore, we studied the effect of nutrition before and during cardiac surgery on myocardial inflammatory response. In this trial, 32 patients were randomised between enteral, parenteral, and no nutrition supplementation (control) from 2 days before, during, up to 2 days after coronary artery bypass grafting. Both solutions included proteins or amino acids, glucose, vitamins, and minerals. Myocardial atrial tissue was sampled before and after revascularization and was analysed immunohistochemically, subdivided into cardiomyocytic, fatty, and fibrotic areas. Inflammatory cells, especially leukocytes, were present in cardiac tissue in all study groups. No significant differences were found in the myocardial inflammatory response between the enteral, parenteral, and control groups. In conclusion, nutrition given before and during surgery neither stimulates nor diminishes the myocardial inflammatory response in patients undergoing coronary artery bypass grafting. The trial was registered in Netherlands Trial Register (NTR): NTR2183.